New Data on the Affinity between the Moscow and Kirillo-Belozersky Redactions of the Verse Prologue (September–November) - Чистякова, Марина Владимировна Владимировна (Slavistica Vilnensis, 2015)
This study of the newly discovered manuscript from the Kirillo-Belozersky redaction of the Verse Prologue (Russian National Library, Kirillo-Belozersky collection 12.1251, XVI–XVII cc.) shows that the composition of the lives of the saints and sermons in the Moscow and Kirillo-Belozersky redactions for September are virtually identical. In comparison with the Moscow redaction, the Kirillo-Belozersky redaction contains several new homilies for October and several new homiletic texts for November, while systematically omitting many of the November sermons of the Moscow redaction. This leads to the conclusion that the idea of producing the Kirillo-Belozersky redaction gradually came into being in the course of copying the manuscript from the Moscow redaction.